RESEARCH IN PRACTICE, TAKE TWO - Wilbraham, Lindy (PINS-Psychology in Society, 2025)
Terre Blanche, M, Durrheim, K and Painter, D (eds) (2006) Research in practice: Applied methods for the social sciences, 2nd edition. Cape Town: UCT Press. ISBN 1-9197-13697 pbk. 594 pages. Research in practice (RIP) has been substantively updated and reworked for its 2nd edition (RIP2). It was previously reviewed in PINS (Parker, 2001), and as a mark of its importance to interdisciplinary worlds of social science, psychologies and research methodology in South Africa (and beyond), it is reviewed again. A second review will inevitably refract inter-textual impressions of new and original versions. The text remains a courageous, sprawling trawl through the complex research-dialogues produced by “proliferation of radically divergent philosophies and techniques” (pviii). Pedagogically, it aims to scaffold soundly argued research processes for students in terms of major paradigms, designs and techniques. To achieve this aim, the editors have reconfigured somewhat haphazard chapters in the original version into more coherent (to my mind) thematic sections. Thus, Section 1 provides a broad overview of decision-making in the research process. Sections 2 and 3 examine the lore of quantitative and qualitative research practice respectively. Section 4 deals with the real-problems in real-contexts of applied research.